2020
DOI: 10.15407/scine16.03.084
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of 3D Scanning Technologies Into the Field of Criminal Proceedings

Abstract: Introduction. Everyday, hundreds ideas of innovative technologies are developed, and thousands innovative products and services are implemented. The practice of criminal proceedings does not stand aside these processes. In recent years, foreign specialists have been increasingly focusing on 3D scanning technologies and the poten tial of their use in investigations.Problem Statement. The problem of 3D technologies in the criminalistic practice has not been sufficiently developed in Ukrainian science, and the id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 1 publication
0
1
0
Order By: Relevance
“…Considering the indicators for 2021 in relation to the entertainment services market, it is impossible to ignore the impact that COVID-19 infection continues to exert. All areas of activity that relate to the entertainment services market have been affected by the pandemic (Blahuta et al, 2020). Over the past two years, a large number of participants in the ecosystem of high technologies, telecommunications, and entertainment have expressed similar opinions: "pandemic caused changes over the past two years that would have taken about 5-7 years at another time".…”
Section: Resultsmentioning
confidence: 99%
“…Considering the indicators for 2021 in relation to the entertainment services market, it is impossible to ignore the impact that COVID-19 infection continues to exert. All areas of activity that relate to the entertainment services market have been affected by the pandemic (Blahuta et al, 2020). Over the past two years, a large number of participants in the ecosystem of high technologies, telecommunications, and entertainment have expressed similar opinions: "pandemic caused changes over the past two years that would have taken about 5-7 years at another time".…”
Section: Resultsmentioning
confidence: 99%
“…Several studies show that models can serve not only as an addition to cadaver dissection but also can serve as a valuable alternative to natural specimens when access to the cadaveric material is limited [47,48]. Some authors reported that different medical specialists have focused on 3D scanning and printing technologies to enrich the medical education process with modern technologies [49,50]. All 3D technologies complement each other, and their integration can open new possibilities for the creation of new, valuable, and revolutionizing products [51,52].…”
Section: Discussionmentioning
confidence: 99%